Terminological Problems Of Media Education - Kacinová, Viera (Communication Today, 2025)
The article contributes to the clariﬁcation of media education terminology. Media education is relatively new and theoretically unresearched cross-sectional ﬁeld of mass media studies, journalism, pedagogy and other interdis-ciplinary sciences. In the context of selected theoretical approaches we propose deﬁnitions of basic concepts of media education while attempting their further terminological analysis. The article also explains some problem areas in the terminology in question.